Ethnobotany of Heracleum persicum Desf. ex Fisch., an invasive species in Norway, or how plant names, uses, and other traditions evolve - Alm, Torbjørn (Journal of Ethnobiology and Ethnomedicine, 2013)
Heracleum persicum was introduced to Norway as an ornamental in the 1830′s. Towards the end of the 19th century, it started spreading outside gardens, later to become a frequent sight in the major towns and settlements of North Norway – and a veritable pest plant. During the last 100 years or so, a substantial ethnobotanical tradition related to the species has evolved, demonstrating that folk knowledge is not only forgotten and lost, but also charting new terrain. This survey is based on data extracted from all relevant publications, including botanical literature, travel accounts, newspaper notes, etc., as far as they have come to my attention. In addition, information on vernacular names and various uses of the H. persicum in Norway has been extracted from my own, substantial archive of interviews, questionnaires, and correspondence related to the ethnobotany of Norway. Where extant, H. persicum tends to be known to everyone, even by city dwellers who otherwise generally neglect plants. People tend to love or hate it, and in Tromsø, the largest town of northern Norway, the species has become more or less emblematic of the city. Both here and in other areas of northern Norway, it is referred to by a variety of vernacular names, partly borrowed from other species, partly derived from the Latin genus name, and partly coined for this species only. In the latter group, tromsøpalme (‘the palm of Tromsø’) has proved by far the most popular invention. It was seemingly first used (and coined) by German soldiers during the World War II occupation of Norway, but now largely replaces other vernacular names. The plant is still popular with children, who frequently play in and with it, whereas adults have been more prone to speculate on its origins – and how to get rid of it. Salt is the most popular “herbicide” for this purpose. Over the years, H. persicum has accumulated at least twenty different vernacular names in Norway, and a variety of other traditions. By necessity, all these traditions are less than 180 years old, ...